Doped lithium-rich manganese oxide positive electrode material and preparation method and application thereof

By introducing rare earth cations into lithium-rich manganese oxide cathode materials to stabilize lattice oxygen and optimize charge distribution, the problems of structural instability and oxygen release in lithium-rich manganese-based materials at high voltages are solved, achieving high energy density and long-term performance. Cycle life compatibility.

CN119361676APending Publication Date: 2025-01-24ZHEJIANG UNIV +1

Patent Information

Application Number
CN202411694548.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Lithium-rich manganese-based positive electrode material will undergo transition metal migration and structural phase transition during high voltage charging and discharging, resulting in irreversible capacity loss. Oxygen peroxidation will also cause rapid attenuation of battery capacity and voltage, and insufficient rate performance, which limits its Potential in fast charging applications.

Method used

By introducing rare earth cations, stabilize the lattice oxygen in lithium -rich materials, and improve the stability of the crystal structure of the material. Rare earth ions such as ND, GD, and DY can inhibit the activity of oxygen, optimize the distribution of charge, reduce the phenomenon of oxygen release under high voltage, and improve the cycle stability and magnification performance of the material by forming a stable lithium-oxygen-rare earth network.

Benefits of technology

It significantly improves the structural stability of lithium-rich manganese oxide cathode materials, extends cycle life, improves rate performance, and achieves high energy density compatibility, making it suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361676A_ABST
    Figure CN119361676A_ABST
Patent Text Reader

Abstract

The invention discloses a doped lithium-rich manganese oxide positive electrode material and a preparation method and application thereof, the chemical general formula of the doped lithium-rich manganese oxide positive electrode material is LiaMnbM (1-b) RExO2 + b, a is more than or equal to 1.0 and less than or equal to 2.5, 0.2 lt; b is less than or equal to 1, 0.0001 lt; xlt; m is one or more of Ni, Co, Mn, Ti, Cr, Fe, Al, Nb and Ru, and RE is at least one of Nd, Sm, Gd, Dy, Ho, Er, Tm and Lu. According to the positive electrode material, lattice oxygen in a lithium-rich manganese material is stabilized by introducing rare earth cations, so that the crystal structure stability of the material is improved, and the compatibility of high energy density and long cycle life of the lithium-rich manganese oxide positive electrode material is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a doped lithium-rich manganese oxide positive electrode material and a preparation method and application thereof. Background Art

[0002] In the field of lithium-ion batteries, cathode materials are key components of batteries. Their performance directly affects the specific energy, safety and cycle life of the battery. Breaking through the capacity limitations of cathode materials is crucial to promoting the development of high-energy-density lithium-ion batteries. Traditional cathode materials (such as nickel-cobalt-manganese ternary, lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, etc.) are gradually unable to meet the rapidly growing demand for high-energy-density energy storage and long-range electric vehicles. The lithium-rich manganese-based cathode material xLi2MnO3·(1-x)LiMO2 (M represents metal elements such as Ni, Co, and Mn) has a high theoretical specific capacity (>350mAh g-1), a unique two-phase structure and oxygen anion redox mechanism, and is an ideal cathode material for the development of high-energy-density lithium-ion batteries.

[0003] However, transition metal migration and structural phase transformation will occur in lithium-rich manganese-based positive electrode materials during high voltage charge and discharge, resulting in irreversible capacity loss. Secondly, during the charge and discharge cycle, oxygen peroxidation will occur in lithium-rich manganese-based positive electrode materials, accompanied by oxidative decomposition of the electrolyte, and the capacity and voltage of the battery will decay rapidly. In addition, the rate performance of lithium-rich manganese materials needs to be improved. Under high-rate charge and discharge, the capacity of the material decays rapidly, limiting its potential in fast charging applications. At present, the modification methods of lithium-rich manganese materials are mainly focused on stabilizing the crystal structure of the material and improving the electrochemical properties by bulk doping with transition metal elements, such as adding aluminum, titanium, magnesium and other elements to improve the conductivity and stability of the material; or by coating the surface with structurally stable materials (such as oxides, phosphates, etc.) to inhibit the side reactions between high-valent metal cations and active oxygen species on the surface of the positive electrode material and the electrolyte to prevent the escape of active oxygen. However, these methods have not completely overcome the problem of limited long cycle life of lithium-rich manganese-based materials, and there may be problems such as complex processes and high costs in large-scale production.

[0004] CN116682972A uses lithium-rich manganese-based positive electrode materials double-modified with selenium and lithium aluminum titanium phosphate to improve the first-cycle coulomb efficiency and cycle stability of lithium-rich manganese-based positive electrode materials; CN113451582A uses metal zirconium oxide and conductive polymer co-coating to prepare structural stabilizers and interface properties of lithium-rich manganese-based materials with core-shell structures. However, in the prior art, oxygen release is prone to occur during the charge and discharge process of lithium-rich manganese-based positive electrode materials, resulting in irreversible structural changes and reducing the electrochemical performance of the material.

[0005] Therefore, how to effectively optimize and modify the lithium-rich manganese-based cathode material to achieve the compatibility of high energy storage density and long cycle life of the lithium-rich manganese-based cathode material is a key problem that urgently needs to be solved in this field. Summary of the Invention

[0006] The present invention provides a doped lithium-rich manganese oxide cathode material. By introducing rare earth cations, the lattice oxygen in the lithium-rich manganese material is stabilized, the crystal structure stability of the material is improved, and the compatibility of high energy density and long cycle life of the lithium-rich manganese oxide cathode material is achieved.

[0007] The present invention provides a doped lithium-rich manganese oxide cathode material, and the chemical general formula of the doped lithium-rich manganese oxide cathode material is Li a Mn b M (1-b) RE x O 2+b , 1.0 ≤ a ≤ 2.5, 0.2 < b ≤ 1, 0.0001 < x < 0.5, M is one or more of Ni, Co, Mn, Ti, Cr, Fe, Al, Nb, Ru, and RE is at least one of Nd, Sm, Gd, Dy, Ho, Er, Tm, Lu.

[0008] Preferably, the rare earth (RE) is one or more of Nd, Gd, and Dy.

[0009] Nd, Gd, and Dy have a high bonding strength with oxygen, can inhibit the activity of oxygen, optimize the charge distribution inside the electrode, can significantly enhance the lattice stability of the material, and reduce the oxygen release phenomenon under high voltage. Optimize the charge distribution. In addition, the ionic radii of Nd, Gd, and Dy are relatively close to those of transition metals Mn and Ni, and their coordination relationship with the lattice is more suitable, and they can be effectively embedded in the lattice without causing serious structural distortion. Rare earth elements with too large or too small ionic radii may lead to an increase in lattice stress and damage the structural stability. Introducing Nd, Gd, and Dy has good comprehensive effects in terms of oxygen structure stability, electron conductivity optimization, cycle life extension, and rate performance improvement. Other rare earth elements (such as Ce, Pr) may perform better in some aspects, but the overall performance improvement is not as balanced as that of Nd, Gd, and Dy.

[0010] Preferably, the mass percentage of Li is: 1 ≤ a ≤ 1.5, and the mass percentage of RE is: 0.001 < x < 0.05.

[0011] An appropriate excess of lithium ions can fill the vacancies that may be left by manganese, nickel or oxygen ions in the lattice, reduce oxygen defects and oxygen release, maintain the integrity of the layered structure of the material, inhibit irreversible phase changes, and help activate the lithium transition metal redox reaction in the material to increase capacity release. Excessive lithium content (a>1.5) will cause uneven ion distribution in the crystal, leading to lattice distortion and stress accumulation, and will also cause a decrease in the ratio of manganese and nickel in the material, affecting the redox capacity of the positive electrode material. In addition, excess lithium volatilizes in the form of lithium oxide, forming by-products on the surface of the material, affecting the interface stability and cycle performance. Insufficient lithium content (a<1) will lead to a lack of sufficient lithium ions in the material to participate in the charge and discharge process, resulting in more oxygen vacancies and lattice oxygen release, limiting capacity release and accelerating material performance degradation.

[0012] Low rare earth content cannot form a uniformly distributed rare earth-oxygen network, and it is difficult to significantly enhance the structural stability of the material. The amount of rare earth ions doped in the lattice is insufficient, and the oxygen release and irreversible phase transition in the crystal cannot be effectively inhibited, and the inhibitory effect on side reactions at the interface is not obvious. Excessive rare earth doping may lead to increased lattice stress and even cause local lattice distortion, destroy the layered structure of the material, and affect the migration path of lithium ions. Excessive rare earth doping will reduce the content of manganese and nickel, thereby reducing the redox activity of the material and increasing the impedance of electron and ion transmission. In addition, the price of rare earth elements is relatively high, and excessive doping will significantly increase production costs, which is not conducive to industrial applications.

[0013] The coordinated regulation of lithium and rare earth content can form a stable lithium-oxygen-rare earth (Li-O-RE) network in the crystal, in which excess lithium fills oxygen vacancies, while rare earth ions inhibit oxygen release by enhancing RE-O bond energy. The combined action of lithium ions and rare earth ions can effectively reduce irreversible lattice collapse. The ratio of rare earth doping to excess lithium needs to be coordinated. Appropriate lithium excess ensures the high capacity of the material, while rare earth doping optimizes the migration path of lithium ions while enhancing structural stability and reducing polarization effects. Appropriate excess lithium reduces the generation of oxygen vacancies, while rare earth elements reduce the activity of lattice oxygen through RE-O bonds and electronic regulation in the lattice. The synergistic effect of the two significantly inhibits oxygen release and interface side reactions.

[0014] On the other hand, the present invention also provides a method for preparing the doped lithium-rich manganese oxide positive electrode material, comprising:

[0015] The lithium-rich manganese oxide positive electrode material precursor is heat-treated and decomposed to obtain a lithium-rich manganese oxide material, and the lithium-rich manganese oxide material and the rare earth compound are evenly mixed according to the mass percentage of each component of the doped lithium-rich manganese oxide positive electrode material, and the doped lithium-rich manganese oxide positive electrode material is obtained after high-temperature calcination.

[0016] Preferably, the method for preparing the lithium-rich manganese oxide positive electrode material precursor includes a coprecipitation method, a sol-gel method, a spray drying method, a combustion method, a solid phase method or a molten salt method.

[0017] Further preferably, the lithium-rich manganese positive electrode substrate precursor prepared by spray drying comprises the following steps:

[0018] The raw materials are prepared according to the molar percentage of each component of the doped lithium-rich manganese oxide positive electrode material, and then added into deionized water to form a mixed solution, a complexing agent is added into the mixed solution, and the mixture is stirred to obtain a metal salt precursor solution;

[0019] The metal salt precursor solution is sprayed, dried and ground by a spray drying method to obtain a lithium-rich manganese positive electrode substrate precursor.

[0020] Further preferably, the raw materials are lithium source, manganese source, nickel source and cobalt source;

[0021] The lithium source is one or more of lithium acetate, lithium fluoride, lithium nitrate, lithium sulfate, lithium chloride, and lithium hydroxide;

[0022] The nickel source is one or more of nickel sulfate, nickel nitrate, nickel acetate, and nickel chloride;

[0023] The cobalt source is one or more of cobalt sulfate, cobalt nitrate, cobalt acetate, and cobalt chloride;

[0024] The manganese source is one or more of manganese sulfate, manganese nitrate, manganese acetate and manganese chloride.

[0025] Further preferably, the raw materials are nickel acetate, manganese acetate and lithium acetate.

[0026] Preferably, the pyrolysis temperature is 100-800° C., and the heat treatment time is 0.5-10 hours.

[0027] Preferably, the rare earth compound is one or more of rare earth carbonates, rare earth nitrates, rare earth acetates, rare earth phosphates, and rare earth complexes.

[0028] Further preferably, the rare earth compound is a rare earth carbonate.

[0029] Further preferably, the rare earth compound is selected from one or more of neodymium carbonate, gadolinium carbonate and dysprosium carbonate.

[0030] Preferably, the molar ratio of the lithium-rich manganese oxide material to the rare earth compound is 1:0.0001-0.5.

[0031] Preferably, the mixing method is grinding, ball milling, mechanical stirring or magnetic stirring.

[0032] Preferably, the atmosphere of the high-temperature calcination is air, oxygen or vacuum, the calcination temperature is 700-1100° C., and the treatment time is 5-24 hours.

[0033] Preferably, the lithium-rich manganese oxide material is a cobalt-free lithium-rich manganese oxide material, and the cobalt-free lithium-rich manganese oxide material is 0.5Li2MnO3 or 0.5LiNi 0.5 Mn 0.5 O2.

[0034] On the other hand, the present invention also provides an application of the doped lithium-rich manganese oxide positive electrode material in a lithium-ion battery, wherein an electrode sheet prepared with the doped lithium-rich manganese oxide positive electrode material is assembled with a negative electrode, a separator and an electrolyte to obtain a lithium-ion battery.

[0035] Preferably, the negative electrode is a graphite carbon negative electrode, a silicon-based negative electrode, a metal oxide negative electrode, a lithium metal negative electrode, etc.; the electrolyte also adopts an organic electrolyte commonly used in the art, including a lithium salt and an organic solvent, and the lithium salt is one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), and lithium bistrifluoromethylsulfonyl imide (LiTFSI); the organic solvent is one or more of dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC), and vinylene carbonate (VC).

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] The present invention stabilizes the lattice oxygen of the lithium-rich manganese oxide by introducing rare earth ions that form strong energy with oxygen, thereby improving the phase structure stability of the material; in addition, the special 4f electron transition energy of the rare earth ions can compensate for the charge balance of the lithium-rich manganese material in the deep delithiation state, prevent irreversible oxygen release caused by oxygen overoxidation, effectively improve the structural stability of the lithium-rich manganese oxide positive electrode material during the charge and discharge process, and improve the cycle stability and rate performance of the material.

[0038] The preparation method of the doped lithium-rich manganese oxide positive electrode material disclosed in the present invention is a conventional mixing and calcination method in the art. The doped lithium-rich manganese oxide positive electrode material is obtained in one step by introducing rare earth ions into the bulk structure during the calcination process of the lithium-rich manganese oxide. The preparation process is simple, controllable, and suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 is a scanning electron microscope (SEM) image of the lithium-rich manganese oxide in Example 1 of the present invention;

[0040] Figure 2 The cycle performance curve of the battery assembled in Example 1 at a current density of 1C (200 mA / g);

[0041] Figure 3 The discharge median voltage curve of the battery assembled in Example 1 during the cycle process;

[0042] Figure 4 The cycle performance curve of the battery assembled in Example 7 at a current density of 1C (200 mA / g);

[0043] Figure 5 The cycle performance curve of the battery assembled in Example 7 at a current density of 1C (200 mA / g);

[0044] Figure 6 The cycle performance curve of the battery assembled in Comparative Example 1 at a current density of 1C (200 mA / g);

[0045] Figure 7 This is a cycle performance curve of the battery assembled in Comparative Example 2 at a current density of 1C (200 mA / g). DETAILED DESCRIPTION

[0046] The present invention is further described below with reference to the examples, but the scope of the present invention is not limited thereto. The materials involved in the examples are all commercially available products.

[0047] Example 1

[0048] The lithium-rich manganese-based positive electrode material was prepared by spray drying combined with high-temperature solid-phase sintering. Specifically, 19.47 g of lithium acetate dihydrate (99.9%), 7.46 g of nickel acetate tetrahydrate (99.9%) and 22.06 g of manganese acetate tetrahydrate (99.9%) were weighed according to the molar ratio of Li:Ni:Mn=1.272:0.2:0.6, and added to 1 L of deionized water to form 0.15 mol L -1 Then add 63.04 g of citric acid monohydrate (99.5%, 0.3 mol L -1 ) as a complexing agent, mechanical stirring combined with ultrasonic treatment for 10 minutes to obtain a transparent metal salt precursor solution. Then, a peristaltic pump was used to deliver the reaction solution to the nozzle of a spray dryer, the peristaltic pump speed was set to 15 rpm, the inlet temperature was set to 230°C, and the outlet temperature was set to 100°C to obtain a spray-dried lithium-rich manganese precursor.

[0049] The spray-dried lithium-rich manganese precursor was heated at 3 °C min -1 The mixture was heated to 500°C and calcined for 5 hours. After cooling in the furnace, it was ground and mixed with gadolinium carbonate according to Ni:Mn:Gd=0.2:0.6:0.005. The resulting mixture was placed in a muffle furnace under air atmosphere at 3°C ​​min -1The temperature was raised to 900 °C and calcined for 10 h, and then ground during furnace cooling to obtain gadolinium-doped Li 1.2 Mn 0.6 Ni 0.2 O2 positive electrode material, denoted as Li 1.2 Mn 0.6 Ni 0.2 O2-0.005Gd.

[0050] The prepared lithium-rich manganese-based cathode material and Super P conductive agent were ground and mixed in a mass ratio of 8:1, and a 1wt% carboxymethyl cellulose (CMC) aqueous solution was prepared as a binder. The ground mixture and CMC were magnetically stirred for 4 h and ultrasonically dispersed for 30 min in a mass ratio of 90:5 to form a uniform slurry, which was then coated on an aluminum foil current collector cleaned with hydrochloric acid and anhydrous ethanol. The cathode sheet was obtained after vacuum drying at 110°C and pressing at 10MPa. The active material loading of all the electrode sheets was 2.0±0.5mg cm -2 The electrochemical performance was tested by assembling Cr2025 button cells, with metal lithium sheets as counter electrodes, Celgard-2400 as diaphragms, and LiPF6 (1 mol L -1 ) of EC / DEC / EMC (volume ratio of 1:1:1) solution were assembled in a glove box filled with argon (water and oxygen content were both less than 0.1ppm). The test voltage window was 2.0-4.8V, and the electrochemical performance of the battery was tested by constant current charge and discharge.

[0051] Example 2-3

[0052] The preparation process of the lithium-rich manganese positive electrode sheet and the assembly test conditions of the button cell of Example 2-3 are the same as those of Example 1. The difference from Example 1 is that the lithium-rich manganese-based positive electrode material and gadolinium carbonate are mixed and calcined according to the molar ratio of Ni:Mn:Gd of 0.2:0.6:0.01 and 0.2:0.6:0.03, respectively, to obtain the gadolinium-doped Li 1.2 Mn 0.6 Ni 0.2 O2 positive electrode materials, respectively denoted as Li 1.2 Mn 0.6 Ni 0.2 O2-0.01Gd and Li 1.2 Mn 0.6 Ni 0.2 O2-0.03Gd.

[0053] Example 4

[0054] Example 4 Preparation process of lithium-rich manganese positive electrode sheet and assembly test conditions of button cell are the same as those of Example 1. The difference from Example 1 is that the lithium-rich manganese-based positive electrode material and neodymium carbonate are weighed and fully mixed and calcined according to the molar ratio of Ni:Mn:Nd=0.2:0.6:0.005 to obtain neodymium-doped Li 1.2 Mn 0.6 Ni 0.2 O2 positive electrode material, denoted as Li 1.2 Mn 0.6 Ni 0.2 O2-0.005Nd.

[0055] Embodiment 5-6

[0056] The preparation process of the lithium-rich manganese positive electrode sheet and the assembly test conditions of the button cell of Example 5-6 are the same as those of Example 1. The difference from Example 1 is that the lithium-rich manganese-based positive electrode material and neodymium carbonate are mixed and calcined according to the molar ratio of Ni:Mn:Nd of 0.2:0.6:0.01 and 0.2:0.6:0.03, respectively, to obtain the neodymium-doped Li 1.2 Mn 0.6 Ni 0.2 O2 positive electrode materials, respectively denoted as Li 1.2 Mn 0.6 Ni 0.2 O2-0.01Nd and Li 1.2 Mn 0.6 Ni 0.2 O2-0.03Nd.

[0057] Example 7

[0058] The preparation process of the lithium-rich manganese positive electrode sheet and the assembly test conditions of the button cell of Example 7 are the same as those of Example 1. The difference from Example 1 is that the lithium-rich manganese-based positive electrode material and dysprosium carbonate are weighed and fully mixed and calcined according to the molar ratio of Ni:Mn:Dy=0.2:0.6:0.005 to obtain the dysprosium-doped Li 1.2 Mn 0.6 Ni 0.2 O2 positive electrode material, denoted as Li 1.2 Mn 0.6 Ni 0.2 O2-0.005Dy.

[0059] Embodiment 5-6

[0060] The preparation process of the lithium-rich manganese positive electrode sheet and the assembly test conditions of the button cell of Example 5-6 are the same as those of Example 1. The difference from Example 1 is that the lithium-rich manganese-based positive electrode material and dysprosium carbonate are mixed and calcined according to the molar ratio of Ni:Mn:Dy of 0.2:0.6:0.01 and 0.2:0.6:0.03, respectively, to obtain the dysprosium-doped Li 1.2 Mn0.6 Ni 0.2 O2 positive electrode materials, respectively denoted as Li 1.2 Mn 0.6 Ni 0.2 O2-0.01Dy and Li 1.2 Mn 0.6 Ni 0.2 O2-0.03Dy.

[0061] Example 8

[0062] The preparation process of the lithium-rich manganese positive electrode sheet and the assembly test conditions of the button cell of Example 8 are the same as those of Example 1. The difference from Example 1 is that the lithium-rich manganese material, neodymium carbonate and gadolinium carbonate are weighed according to the molar ratio of Ni:Mn:Nd:Gd=0.2:0.6:0.005:0.005, and the mixture is fully mixed and calcined to obtain the neodymium and gadolinium co-doped Li 1.2 Mn 0.6 Ni 0.2 O2 positive electrode material, denoted as Li 1.2 Mn 0.6 Ni 0.2 O2-0.005Nd-0.005Gd.

[0063] Comparative Example 1

[0064] Comparative Example 1 Spray drying of lithium-rich manganese precursor is the same as in Example 1, except that the lithium-rich manganese precursor is placed in a muffle furnace under air atmosphere at 3°C ​​min -1 Heat to 900℃ and calcine for 10h, then grind to obtain Li 1.2 Mn 0.6 Ni 0.2 O2 cathode material,

[0065] Comparative Example 2

[0066] Comparative Example 2 The spray-dried lithium-rich manganese precursor is the same as that of Example 1, except that the spray-dried lithium-rich manganese precursor is heated at 3°C ​​min -1 Heat to 500℃ and calcine for 5h. After cooling in the furnace, grind and place in a muffle furnace under air atmosphere at 3℃min -1 Heat to 900℃ and calcine for 10h, then grind to obtain Li 1.2 Mn 0.6 Ni 0.2 O2 positive electrode material.

[0067] Figure 1This is a scanning electron microscope (SEM) image of the lithium-rich manganese oxide in Example 1. It can be seen that the lithium-rich manganese oxide material is composed of polyhedral nanoparticles with a uniform size of 100 to 200 nm. The lithium ions in the material nanoparticles can diffuse quickly into the interior, reducing the diffusion impedance. The smaller particle size shortens the migration path of lithium ions from the electrolyte to the active site, significantly improving the capacity release. The surface of the polyhedral particle has multiple crystal planes, which have different ion diffusion rates, which facilitates the multi-directional diffusion of lithium ions and avoids the limitation of a single diffusion path.

[0068] Figure 2 The cycle performance curve of the battery assembled in Example 1 at a current density of 1C (200 mA / g). During the cycle, the discharge capacity increases slowly in the initial stage, and after 400 cycles, it can still release a capacity of 179 mAh / g, with a capacity retention rate of 97%, showing good cycle stability. Figure 3 This is the discharge median voltage curve during the cycle of the battery assembled in Example 1. The results show that the discharge median voltage of the material in this example is 3.13V after 400 cycles, and the retention rate is 88%.

[0069] Figure 4 The cycle performance curve of the battery assembled in Example 7 at a current density of 1C (200 mA / g) is shown. During the cycle, the discharge specific capacity increases slowly in the initial stage, and after 400 cycles, it can still release a specific capacity of 173 mAh / g, with no obvious capacity attenuation, showing good cycle stability. Figure 5 This is the discharge median voltage curve during the cycle of the battery assembled in Example 7. The results show that the discharge median voltage of the material in this example is 3.21V after 400 cycles, and the retention rate is 91%.

[0070] Figure 6 The cycle performance curve of the battery assembled in Comparative Example 1 at a current density of 1C (200 mA / g). During the cycle, the discharge specific capacity decayed rapidly, and after 400 cycles, a specific capacity of 53 mAh / g was released, and the capacity retention rate was 28%, indicating that the lithium-rich manganese oxide material without the introduction of rare earth elements has poor cycle stability.

[0071] Figure 7 The cycle performance curve of the battery assembled in Comparative Example 2 at a current density of 1C (200mA / g). During the cycle, the discharge specific capacity gradually decreased, and after 400 cycles, a specific capacity of 152mAh / g was released, and the capacity retention rate was 83%, indicating that the cycle stability of the lithium-rich manganese oxide material without the introduction of rare earth elements was improved to a certain extent after the intermediate heat treatment at 500°C.

Claims

1. A doped lithium-rich manganese oxide positive electrode material, characterized in that: The chemical general formula of the doped lithium-rich manganese oxide cathode material is Li a Mn b M (1-b) RE x O 2+b , where 1.0 ≤ a ≤ 2.5, 0.2 < b ≤ 1, 0.0001 < x < 0.5, M is at least one of Ni, Co, Mn, Ti, Cr, Fe, Al, Nb, Ru, and RE is at least one of Nd, Sm, Gd, Dy, Ho, Er, Tm, Lu.

2. The doped lithium-rich manganese oxide positive electrode material according to claim 1, characterized in that: The rare earth is one or more of Nd, Gd and Dy.

3. The doped lithium-rich manganese oxide positive electrode material according to claim 1, characterized in that: The mass percentage of Li is: 1≤a≤1.5, and the mass percentage of RE is: 0.001 <x<0.05。 4. A method for preparing a doped lithium-rich manganese oxide positive electrode material according to any one of claims 1 to 3, characterized in that: include: The lithium-rich manganese oxide positive electrode material precursor is heat-treated and decomposed to obtain a lithium-rich manganese oxide material, and the lithium-rich manganese oxide material and the rare earth compound are evenly mixed according to the mass percentage of each component of the doped lithium-rich manganese oxide positive electrode material, and the doped lithium-rich manganese oxide positive electrode material is obtained after high-temperature calcination.

5. The method for preparing a doped lithium-rich manganese oxide positive electrode material according to claim 4, characterized in that: The methods for preparing the lithium-rich manganese oxide positive electrode material precursor include coprecipitation method, sol-gel method, spray drying method, combustion method, solid phase method or molten salt method.

6. The method for preparing a doped lithium-rich manganese oxide positive electrode material according to claim 5, characterized in that: The lithium-rich manganese positive electrode substrate precursor prepared by spray drying comprises the following steps: The raw materials are prepared according to the molar percentage of each component of the doped lithium-rich manganese oxide positive electrode material, and then added into deionized water to form a mixed solution, a complexing agent is added into the mixed solution, and the mixture is stirred to obtain a metal salt precursor solution; The metal salt precursor solution is sprayed, dried and ground by a spray drying method to obtain a lithium-rich manganese positive electrode substrate precursor.

7. The method for preparing a doped lithium-rich manganese oxide positive electrode material according to claim 4, characterized in that: The raw materials are lithium source, manganese source, nickel source and cobalt source; The lithium source is one or more of lithium acetate, lithium fluoride, lithium nitrate, lithium sulfate, lithium chloride, and lithium hydroxide; The nickel source is one or more of nickel sulfate, nickel nitrate, nickel acetate, and nickel chloride; The cobalt source is one or more of cobalt sulfate, cobalt nitrate, cobalt acetate, and cobalt chloride; The manganese source is one or more of manganese sulfate, manganese nitrate, manganese acetate and manganese chloride.

8. The method for preparing a doped lithium-rich manganese oxide positive electrode material according to claim 7, characterized in that: The raw materials are nickel acetate, manganese acetate and lithium acetate.

9. The method for preparing a doped lithium-rich manganese oxide positive electrode material according to claim 4, characterized in that: The rare earth compound is one or more of rare earth carbonates, rare earth nitrates, rare earth acetates, rare earth phosphates, and rare earth complexes.

10. Use of the doped lithium-rich manganese oxide positive electrode material according to any one of claims 1 to 3 in a lithium-ion battery, wherein an electrode sheet prepared with the doped lithium-rich manganese oxide positive electrode material is assembled with a negative electrode, a separator and an electrolyte to obtain a lithium-ion battery.

Citation Information

Patent Citations

  • Rare-earth-doped lithium-rich layered lithium ion battery cathode material and preparation method thereof

    CN103208620A

  • Rare earth element modified lithium ion battery positive electrode material and preparation method and application thereof

    CN110911687A

  • Yttrium-doped lithium-rich manganese-based lithium ion battery positive electrode material, preparation method thereof and lithium ion battery

    CN111082044A

  • Sodium and lanthanum co-doped modified lithium-rich manganese-based positive electrode material and preparation method thereof

    CN116093303A

  • Multiphase composite layered manganese-based positive electrode material and preparation method thereof

    CN116154174A

Cited By

  • Lithium ion battery manganese-rich positive electrode material, preparation method and application

    CN120987383A

  • Doped lithium-rich manganese-based positive electrode material and preparation method thereof

    CN121331815A